Amérique Septentrionale. - Jacobs, S. (Fosset, 1867)
Map shows major cities and notable physical features for North America; "Territoire D'Alaska," "Nouvelle Bretagne" [Canada], Groenland, the United States, Mexico, Central America mainly as Guatemala, and the Antilles; areas of Native American habitation; undivided island of Haiti; coloration of U.S. Mexico boundary line along Gila River, old dotted-line boundary at forty-second degree line of latitude still visible. Relief shown by hachures. Scale not given.